2013
DOI: 10.4103/0972-0707.105298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bleaching with two different concentrations of hydrogen peroxide containing sweet potato extract as an additive on human enamel: An in vitro spectrophotometric and scanning electron microscopy analysis

Abstract: Objectives:To evaluate the color change in teeth bleached with two different concentrations of hydrogen peroxide, containing sweet potato extract as an additive, using a spectrophotometer, and to evaluate the surface changes in enamel using a scanning electron microscope (SEM).Materials and Methods:Baseline color values of 24 artificially stained incisors were obtained using a spectrophotometer. The specimens were divided into two groups of 12 teeth, each based on the concentration of hydrogen peroxide (H2O2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
9
1
Order By: Relevance
“…[ 18 ] In this study, although all products under evaluation were home-bleaching systems with similar CP concentrations, it could be observed that there were differences in efficacy between these products, mainly due to the application time and different active ingredients except CP in these products. [ 39 40 ] Contrary to expectations, it is shown in this study that the application time of the bleaching gel is not directly related with the bleaching efficacy of the systems. [ 41 ] Furthermore, the statistical insignificant difference between SG-1 and SG-2, shows 1 h of application time is enough to achieve desired level of bleaching.…”
Section: Discussioncontrasting
confidence: 68%
“…[ 18 ] In this study, although all products under evaluation were home-bleaching systems with similar CP concentrations, it could be observed that there were differences in efficacy between these products, mainly due to the application time and different active ingredients except CP in these products. [ 39 40 ] Contrary to expectations, it is shown in this study that the application time of the bleaching gel is not directly related with the bleaching efficacy of the systems. [ 41 ] Furthermore, the statistical insignificant difference between SG-1 and SG-2, shows 1 h of application time is enough to achieve desired level of bleaching.…”
Section: Discussioncontrasting
confidence: 68%
“…A rough enamel, with irregularities after bleaching stains more easily (1,8) since food dyes can adhere to rough surface (9). Resultant erosion depths are different with bleaching agents of different pHs, with approximately 0.27µm for 30% H2O2-NaHCO3 (higher pH) and 0.85µm for 35% H2O2 (more acid) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Superficial roughness increases after bleaching and this enhances teeth staining by dye adhesion (8,9). This consequence is more pronounced with colourant food and beverage intake (10).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our study, the use of natural enzymes (polyphenol peroxidase, catalase, and superoxide dismutase) extracted from the sweet potato (Ipomoea batatas L.) recently revealed to positively bleach stained teeth. The authors used the sweet potato extract as an additive to hydrogen peroxide gels, demonstrating that this combination resulted in the restoration of natural tooth color and in reduced alteration of enamel morphology when compared to the use of hydrogen peroxide alone [16]. Regarding this subject, one of the most important advantages of using natural products to whiten teeth rather than using hydrogen/carbamide peroxide-based agents is the less aggressive process produced by the former.…”
Section: Discussionmentioning
confidence: 97%
“…It is worth mentioning that not only hydrogen peroxide molecules are capable of producing an oxidative reaction, but some vegetable-derived enzymes (e.g., polyphenol peroxidase, catalase, superoxide dismutase) have also been known to result in satisfactory stain removal effect [16]. A fairly novel dentifrice containing bromelain and papain, i.e., two proteolytic enzymes, has demonstrated improved ability to remove tooth stains when compared to the control used (i.e., regular dentifrice) [17,18].…”
Section: Introductionmentioning
confidence: 99%